The dependence of sodium pumping and tension on intracellular sodium activity in voltage-clamped sheep Purkinje fibres. - Eisner, D A (1981)
1. Intracellular Na activity (aiNa) was measured in sheep cardiac Purkinje fibres using a recessed-tip Na+-sensitive micro-electrode. The membrane potentials was controlled with a two-micro-electrode voltage clamp. Tension was measured simultaneously. 2. Removing external K produced a rise of aiNa and both twitch and tonic tension. On adding 4-10 mM-[Rb]0 to reactivate the Na-K pump aiNa and tension declined. An electrogenic Na pump current transient accompanied the fall of aiNa. 3. The half-time of decay of the electrogenic Na pump current transient was similar to that of aiNa, (mean tNa0.5/tI0.5 = 0.97 +/- 0.03 (S.E.M.; n = 28)). Following the re-activation of the Na-K pump, the electrogenic Na pump current transient was linearly related to aiNa. 4. The duration of exposure to K-free, Rb-free solutions was varied to change the level of aiNa. On subsequently re-activating the Na-K pump with 10 mM-[Rb]0, the ratio of the charge extruded to the total change of aiNa was constant. It is concluded that the fraction of Na extruded electrogenically is unaffected by changes of aiNa. About 26% of the total Na extrusion appeared as charge transfer. 5. The relationship between tonic tension and aiNa was usually different during Na-K pump inhibition in a K-free, Rb-free solution compared with the relationship during Na-K pump re-activation. In general, a given aiNa was associated with a greater level of tonic tension during Na-K pump inhibition compared with that during pump re-activation. A similar hysteresis was often seen between twitch tension and aiNa.